Synthesis of digestive enzymes, food processing, and nutrient absorption in decapod crustaceans: a comparison to the mammalian model of digestion - Vogt, Günter (Zoology, 2021)
The ∼15.000 decapod crustaceans that are mostly omnivorous have evolved a structurally and functionally complex digestive system. They have highly effective cuticular chewing and filtering structures in the stomach, which are regularly renewed by moulting. Decapods produce a broad range of digestive enzymes including chitinases, cellulases, and collagenases with unique properties. These enzymes are synthesized in the F-cells of the hepatopancreas and are encoded in the genome as pre-pro-proteins. In contrast to mammals, they are stored in a mature form in the lumen of the stomach to await the next meal, and therefore, the enzymes are particularly stable. The fat emulsifiers are fatty acyl-dipeptides rather than bile salts. After mechanical and chemical processing of the food in the cardiac stomach, the chyme is filtered by two unique filter systems of different mesh-size. The filtrate is then transferred to the hepatopancreas where the nutrients are absorbed by the R-cells, mostly via carriers, resembling nutrient absorption in the small intestine of mammals. The absorbed nutrients are used to fuel the metabolism of the hepatopancreas, are supplied to other organs, and are stored in the R-cells as glycogen and lipid reserves. Export lipids are secreted from the R-cells into the haemolymph as high density lipoproteins that mainly consist of phospholipids. In contrast to mammals, the midgut tube and hindgut contribute only little to food processing and nutrient absorption. The oesophagus, stomach and hindgut are well innervated but the hepatopancreas lacks nerves. Hormone cells are abundant in the midgut and hepatopancreas epithelia. Microorganisms are often present in the intestine of decapods, but they are apparently not essential for digestion and nutrition.
Gesehen am 22.08.2021